2014
DOI: 10.1016/j.bbadis.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular and intracellular microRNAs in sepsis

Abstract: Sepsis is the major cause of death in the intensive care unit (ICU). Numerous biomarkers have been studied to identify the cause and severity of sepsis but these factors cannot differentiate between infectious and non-infectious inflammatory response. MicroRNAs (miRNAs) are non-coding RNA transcripts that regulate the expression of genes by repressing translation or degrading mRNA. Importantly, miRNAs can be released outside cells and easily detectable in bodily fluids such as blood, sweat, urine and breast mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 70 publications
0
114
0
Order By: Relevance
“…They confirmed that septic platelet-derived exosomes contain NOS, which can generate NO in exosomes and induce NO production in the heart. More recently, numerous studies have profiled circulating exosomal miRNAs in septic patients [63]. Specifically, the levels of exosomal miR-223 are significantly lower in the blood of non-survival septic patients, compared with survivors [94].…”
Section: Pathological Effects Of Exosomes On Cardiac Remodelingmentioning
confidence: 99%
“…They confirmed that septic platelet-derived exosomes contain NOS, which can generate NO in exosomes and induce NO production in the heart. More recently, numerous studies have profiled circulating exosomal miRNAs in septic patients [63]. Specifically, the levels of exosomal miR-223 are significantly lower in the blood of non-survival septic patients, compared with survivors [94].…”
Section: Pathological Effects Of Exosomes On Cardiac Remodelingmentioning
confidence: 99%
“…Studies have also demonstrated that IGF-1 is regulated by oxidative stress. Notably it has also been demonstrated that IGF-1 levels in blood samples are reduced in the acute phase for critical patients (8). However, it remains unclear whether IGF-1 has an anti-oxidative stress role in sepsis and the association between IGF-1 and the severity or prognosis of patients with sepsis is also ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration in miRNA-223 and miRNA-126 not only relates to CVD, we used two databases (miR2Disease Base and Human microRNA disease database) to relate these miRNA with different diseases. Approximately 50 different diseases are related to these miRNA among which are: muscular disorders [128], leukemia [129,130] and sepsis [131]. Therefore, the alteration in the levels of miRNA in platelets could relate to many diseases and be a potential target for treatment.…”
Section: Resultsmentioning
confidence: 99%